The Legal Framework Governing BUMDes in Indigenous Communities: The Case of the Baduy Community - Mohamad Noor Fajar Al Arif Fitriana; Ahmad Fauzi (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2026)
Village-Owned Enterprises (BUMDes) have emerged as a key instrument of Indonesia’s decentralized rural development strategy, aiming to strengthen local economies and enhance village-generated revenue. However, the implementation of BUMDes within indigenous communities presents unique legal and institutional challenges due to the coexistence of state law and customary governance systems. This study examines the legal framework governing the establishment and management of BUMDes in the Baduy Indigenous Community and analyzes its role in supporting community-based economic development. Employing a socio-normative legal approach, the research combines the analysis of statutory regulations, regional legal instruments, and secondary legal materials with an assessment of their implementation in the Baduy context. The findings demonstrate that the legal basis for BUMDes in the Baduy community is derived from national, ministerial, and regional regulations governing village administration and rural economic enterprises. The study further reveals that the successful introduction of BUMDes depends on the adaptation of institutional arrangements to indigenous values through legal socialization, community participation, and the alignment of business activities with customary norms. The novelty of this research lies in its examination of BUMDes through the lens of legal pluralism, highlighting the interaction between state-based village governance and indigenous customary institutions. The study contributes to the discourse on indigenous economic governance by proposing a legally adaptive model for integrating rural economic development initiatives within customary communities.